1990
DOI: 10.1088/0022-3727/23/2/023
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the energy dependence of electron beam assisted etching of, and deposition on, silica

Abstract: The electron beam assisted etch rates for SiO2 by using XeF2 and CF4 gases were measured as a function of primary electron energy. The deposition rate of Fe on SiO2 substrate with Fe(CO)5 as a source gas was also measured. It is seen that both the etch rate and the deposition rate are higher at lower primary electron energies in the region of 1 keV to 15 keV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
3
8
0
Order By: Relevance
“…We note that the new EBIE model is consistent with all results in the literature that were explained successfully by the conventional EBIE model [1,2,5,[34][35][36][37][38][39][40][41][42][43][44]47]. The scaling of etch rate with beam energy is the same because the secondary electron yield is proportional to the energy transferred from the beam to the surface atoms of the substrate.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…We note that the new EBIE model is consistent with all results in the literature that were explained successfully by the conventional EBIE model [1,2,5,[34][35][36][37][38][39][40][41][42][43][44]47]. The scaling of etch rate with beam energy is the same because the secondary electron yield is proportional to the energy transferred from the beam to the surface atoms of the substrate.…”
supporting
confidence: 84%
“…(1) [2,5,[34][35][36][37][38][39][40][41][42][43][44]. However, the model can not explain the etch rate anisotropy seen in Fig.…”
mentioning
confidence: 99%
“…This result suggests that carbon etching results primarily from a gas-phase ionization mechanism and not lattice activation of carbon through radiolysis. This is consistent with previous reports using XeF2 [15][16][17] in which a decrease in etch efficiency was observed with increasing acceleration voltage. Figure 3 shows the carbon etch rate (volume/time) versus electron fluence at a fixed acceleration voltage (5kV).…”
Section: Resultssupporting
confidence: 93%
“…It was found that in the presence of an electron beam, XeF2 decomposes and locally etches SiO2, Si3N4 and SiC. The technique was extended by Fujioka et al [16] to include Cl2 and ClF gases as etchants. Randolph et al [17] performed detailed studies to further the understanding of the etchant/substrate combination of XeF2/SiO2.…”
Section: Introductionmentioning
confidence: 99%
“…Fujioka et al successfully deposited iron on a SiO 2 substrate by using an Fe͑CO͒ 5 precursor gas. 15 They studied the influence of primary electron energy on the deposition process. By scanning a 50ϫ 100-m 2 area for 60 min, they determined that the deposition rate increased for lower beam energies.…”
Section: Introductionmentioning
confidence: 99%